Dental Resin Monomer Enables Unique NbO2/Carbon Lithium‐Ion Battery Negative Electrode with Exceptional Performance. (16th August 2019) - Ji, Qing; Gao, Xiangwen; Zhang, Qiuju; Jin, Liyu; Wang, Da; Xia, Yonggao; Yin, Shanshan; Xia, Senlin; Hohn, Nuri; Zuo, Xiuxia; Wang, Xiaoyan; Xie, Shuang; et al.
Abstract: Niobium dioxide (NbO2 ) features a high theoretical capacity and an outstanding electron conductivity, which makes it a promising alternative to the commercial graphite negative electrode. However, studies on NbO2 based lithium‐ion battery negative electrodes have been rarely reported. In the present work, NbO2 nanoparticles homogeneously embedded in a carbon matrix are synthesized through calcination using a dental resin monomer (bisphenol A glycidyl dimethacrylate, Bis‐GMA) as the solvent and a carbon source and niobium ethoxide (NbETO) as the precursor. It is revealed that a low Bis‐GMA/NbETO mass ratio (from 1:1 to 1:2) enables the conversion of Nb (V) to Nb (IV) due to increased porosity induced by an alcoholysis reaction between the NbETO and Bis‐GMA. The as‐prepared NbO2 /carbon nanohybrid delivers a reversible capacity of 225 mAh g −1 after 500 cycles at a 1 C rate with a Coulombic efficiency of more than 99.4% in the cycles. Various experimental and theoretical approaches including solid state nuclear magnetic resonance, ex situ X‐ray diffraction, differential electrochemical mass spectrometry, and density functional theory are utilized to understand the fundamental lithiation/delithiation mechanisms of the NbO2 /carbon nanohybrid. The results suggest that the NbO2 /carbon nanohybrid bearing high capacity, long cycle life, and low gas evolution is promising for lithium storage applications. Abstract : Using a dental resin monomer as the solvent and a carbon source enables the formation of unique NbO2 nanoparticles homogeneously embedded in the carbon matrix, where an excellent electrochemical performance in terms of reversible capacities, long cycling life, and limited gassing evolution is demonstrated.